2008
DOI: 10.1021/ie800282f
|View full text |Cite
|
Sign up to set email alerts
|

Voidage and Pressure Profile Characteristics of Sand−Iron Ore−Coal−FCC Single-Particle Systems in the Riser of a Pilot Plant Circulating Fluidized Bed

Abstract: Hydrodynamic behaviors of single system of particles were investigated in a circulating fluidized bed (CFB) unit. Particles belonging to Geldart groups A and B like sand of various sizes (80, 300, 417, 522, 599, and 622 µm), FCC catalyst (120 µm), iron ore (166 and 140 µm), and coal (335 and 168 µm) were used to study the hydrodynamic characteristics. Superficial air velocity used in the present study ranged between 2.01 and 4.681 m/s and corresponding mass fluxes were 12.5-50 kg/(m 2 s). A CFB needs the crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 11 publications
(20 reference statements)
0
21
1
Order By: Relevance
“…This drastic reduction in static pressure may be due to the reasons as explained earlier. The values of static pressure at higher velocity were low compared to a lower velocity [7]. Figure 4 shows the typical effect of the solids circulation rate on the static pressure profile for air-coal at a constant velocity of 2.01 m=s.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This drastic reduction in static pressure may be due to the reasons as explained earlier. The values of static pressure at higher velocity were low compared to a lower velocity [7]. Figure 4 shows the typical effect of the solids circulation rate on the static pressure profile for air-coal at a constant velocity of 2.01 m=s.…”
Section: Resultsmentioning
confidence: 97%
“…It was observed that the effect of gas velocity in the dilute zone was almost negligible but in the dense zone there was a considerable change in voidage. The general tendency for the dense region was to expand with decreasing gas flow at a constant solid circulation rate [7].…”
Section: Hydrodynamics Of Coal In a Cfb Reactor 271mentioning
confidence: 99%
“…Slightly simplified engineering models [30] consider dependence of the dependent variables (ε, ρ f , U p and ΔP PT ) on the axial (vertical) coordinate. If an average (constant) gas density can be considered, the three balance equations for U p , ε and ΔP PT have to be solved [31,32].…”
Section: Simplified Empirical Models For Particle Velocity and Pneumamentioning
confidence: 99%
“…As the flow intermittency is closely related to the heterogeneous distribution of hydrodynamic parameters and the non-equilibrium flow state, which can further result in fluidisation faults such as stagnant zones, hot spots, particle adhesion to the wall, slugs, and even defludisation, it is necessary to understand the hydrodynamic characteristics of the intermittent flow behaviours in a CFB with Geldart A particles. Despite extensive studies conducted on the experimentation and simulation of CFBs with Geldart A particles [3][4][5][6][7][8][9], the knowledge about flow intermittency is still limited. Brereton and Grace [10] derived an intermittency index from the measured suspension density fluctuating signals to quantify the nonuniformity of the flow field in a riser.…”
Section: Introductionmentioning
confidence: 99%